New Online Media Business Models - Angova, Stella; Valchanov, Ivan (UNWE Yearbook, 2018)
This study focuses on identifying the new business models in online media. Documentary analysis of practices for introducing new business models from web-based media has been carried out. Web sites of global media brands and research centers have been observed. The new business models are grouped into five groups in terms of access, content, audience, external organizations, technologies. Each affiliation group lists all the registered 22 current business models of the online media.